COMPARISON OF A NINTENDO WII BALANCE BOARD WITH A LABORATORY-GRADE FORCE PLATE ON MEASUREMENT OF TRANSITIONAL MOVEMENTS (Kinesiology, 2018)
The aim of this study was to verify whether the Nintendo Wii-Balance-Board was valid and reliable for assessing sit-to-stand and return-to-sit tasks by comparing it with a gold-standard force plate. Ten elderly (age = 78.21±14.82 years; males=4; females=6) and eleven young (age =24.25±12.43 years; males=6; females=5) participants of both genders performed five sit-to-stand and return-to-sit tasks consecutively by placing their feet on the Wii-Balance-Board; after two days of rest, they repeated the same assessment. The Wii-Balance- Board was positioned over the force plate to concurrently acquire the vertical component of ground reaction forces. Relevant kinetic and temporal parameters were estimated from these signals. Both the Wii-Balance-Board and force plate measurements resulted in a high level of correlation for almost all the parameters (Pearson’s product-moment r ranged from 0.91 to 0.99, p